2016
DOI: 10.9778/cmajo.20150117
|View full text |Cite
|
Sign up to set email alerts
|

Hospital stays for hepatitis B or C virus infection or primary liver cancer among immigrants: a census-linked population-based cohort study

Abstract: A lthough primary liver cancer (the majority of which is hepatocellular carcinoma) is uncommon in Canada, representing about 1% of all cancers, its incidence has increased threefold since the early 1980s.1,2 Much of this increase has been attributed to a higher proportion of immigrants from countries endemic for the hepatitis B virus (HBV) and, to a lesser extent, the hepatitis C virus (HCV). [3][4][5][6][7] Globally, chronic infection with HBV or HCV, or both, is the underlying cause in about 80% of cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In general, the asymptomatic nature of HBV infection leads to late diagnosis after complications have developed[ 1 ]. Studies have shown that immigrants in Canada are disproportionately affected by HCC and decompensated cirrhosis and have up to 5 times greater risk of death from these causes than their Canadian-born counterparts[ 14 , 30 , 31 ]. Therefore, screening for HBV within the East Asian population is vital for early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the asymptomatic nature of HBV infection leads to late diagnosis after complications have developed[ 1 ]. Studies have shown that immigrants in Canada are disproportionately affected by HCC and decompensated cirrhosis and have up to 5 times greater risk of death from these causes than their Canadian-born counterparts[ 14 , 30 , 31 ]. Therefore, screening for HBV within the East Asian population is vital for early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in the misclassification of East Asians from the Philippines as Whites and in the underestimation of the HBV in East Asian population. Previous studies have shown that foreign-born and Indigenous Canadians have a higher prevalence of chronic HBV relative to Canadian-born and non-Indigenous Canadians, respectively[ 5 , 30 , 38 ]. Similar findings have been reported in Australia and the United States[ 10 , 39 ].…”
Section: Discussionmentioning
confidence: 99%